2021
DOI: 10.22201/fesc.20072236e.2021.12.22.2
|View full text |Cite
|
Sign up to set email alerts
|

Las Competencias Investigativas en estudiantes de la Licenciatura en Contaduría: Un Reto

Abstract: La educación es la base del desarrollo de cualquier nación, ya que el contexto actual exige para la supervivencia de sus sociedades la creación de riqueza basada en el conocimiento. Esto implica la necesidad de que todo gobierno invierta importantes recursos en la formación de docentes, estudiantes, técnicos e investigadores capaces de generar nuevos conocimientos que posibiliten el bienestar social; por tanto, el sistema educativo debe desarrollar competencias investigativas para los procesos de productividad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
0
0
Order By: Relevance
“…Regarding the first dimension, problem statement and theoretical basis, with a high frequency at the basic level, it was commented that students in the issues of the problem statement, information gathering, location, and analysis usually apply it based on their represented knowledge. The works presented in the courses they take, create a seed of growth in the research activities, this is verified with the research evidence, where it was observed that 85% of the students enrolled in the accounting course carried out a written work applying the corresponding scientific regulations 28 .…”
Section: Discussion Of the Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…Regarding the first dimension, problem statement and theoretical basis, with a high frequency at the basic level, it was commented that students in the issues of the problem statement, information gathering, location, and analysis usually apply it based on their represented knowledge. The works presented in the courses they take, create a seed of growth in the research activities, this is verified with the research evidence, where it was observed that 85% of the students enrolled in the accounting course carried out a written work applying the corresponding scientific regulations 28 .…”
Section: Discussion Of the Resultssupporting
confidence: 64%
“…The research design was non-experimental, crosssectional, or correlational. This design was made without deliberately manipulating its variables [27][28] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…El desarrollo de la competencia investigativa ha sido objeto de estudio en distintos programas educativos, tanto de licenciatura (Cangas et al, 2020;Matta, 2017;Parra-Castrillón, 2018;Rodríguez et al, 2020;Sánchez et al, 2021) como de posgrado (Cardoso y Cerecedo, 2019;George y Salado, 2019;Hernández et al, 2018). Al acotar la búsqueda al ámbito del derecho fue posible identificar avances al respecto, explicitamos a continuación.…”
Section: Antecedentes Sobre La Competencia Investigativa En La Formac...unclassified